Antimicrobial Assessment of Resins from Calophyllum Antillanum and Calophyllum Inophyllum. (30th October 2015) - Cuesta‐Rubio, Osmany; Oubada, Ahmad; Bello, Adonis; Maes, Louis; Cos, Paul; Monzote, Lianet
Abstract : The Calophyllum genus is well‐known for its antimicrobial and cytotoxic activities, and therefore, we analyzed these biological activities for resins of Calophyllum antillanum and Calophyllum inophyllum growing in Cuba. C . antillanum resins showed a potent activity against Plasmodium falciparum (IC50 = 0.3 ± 0.1 µg/mL), while its cytotoxicity against MRC‐5 cells was much lower (IC50 = 21.6 ± 1.1 µg/mL). In contrary, the resin of C . inophyllum showed an unspecific activity. The presence of apetalic acid, isoapetalic acid, calolongic acid, pinetoric acid I, pinetoric acid II, isocalolongic acid, pinetoric acid III, and isopinetoric acid III in C . antillanum resins was also confirmed. These results demonstrated for the first time the potential activity of C . antillanum resins against P . falciparum . Copyright © 2015 John Wiley & Sons, Ltd.